2003
DOI: 10.1097/00043426-200305000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Alterations of the Cell Cycle Regulators and Tumor Suppressor Genes in Pediatric Osteosarcomas

Abstract: RB1, TP53, and possibly other tumor suppressor genes located at 18q and other localizations are involved in pediatric osteosarcoma carcinogenesis, together with other genetic alterations not fully understood to date. Based on these results, the presence of an altered RB1 gene should be regarded as a poor prognostic factor for pediatric osteosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
2
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 21 publications
3
42
2
1
Order By: Relevance
“…Genome instabilities have been previously reported in pediatric osteosarcomas, [27][28][29][31][32][33] and a recent study on highgrade osteosarcomas showed a large number of genome alterations, such as 18q or 3q abnormalities, 31 but none of the scored chromosomal altered regions referred to the 7p21 band as a target.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Genome instabilities have been previously reported in pediatric osteosarcomas, [27][28][29][31][32][33] and a recent study on highgrade osteosarcomas showed a large number of genome alterations, such as 18q or 3q abnormalities, 31 but none of the scored chromosomal altered regions referred to the 7p21 band as a target.…”
Section: Discussionmentioning
confidence: 82%
“…The QPCR results were expressed relatively to 2 internal controls: the APP gene, encoding the amyloid precursor protein, implied in Alzheimer's disease, 34 and the DCK gene, deoxycytidine kinase gene, implied in leukemias, 35 but the number of available control genes for cancer studies is reduced because of the frequent genomic rearrangements and instability in the cancers. Published frequencies for rearrangements at APP and DCK were approximately less than 10%, [29][30][31] and could explain the rare discordant patients with allelotyping when normal. Using 2 different techniques, concordant results obtained on almost all the patients highlight the existence of rearrangements at the 7p21 region, and more precisely at the TWIST gene in pediatric osteosarcomas.…”
Section: Discussionmentioning
confidence: 99%
“…Of those, five reports were excluded: four due to lack of any informative clinical data (37)(38)(39)(40), and one because of overlapping with another study (41). Three reports pertained to the same study (22,42,43), and two (42, 43) described outcomes on a subset of patients included in the other study (22). We retained the publication with the larger sample size, but we also used information for 2-year survival from the subset publications because no such data were provided in the publication with the (20) were included in another study (11).…”
Section: Resultsmentioning
confidence: 99%
“…5,6 Other studies have found instances of promoter methylation silencing the genes encoding the p53 regulatory proteins p16INK4A and p14ARF (both encoded by the CDKN2A gene). [7][8][9] However, few genome-wide studies on patient samples have been reported, 10,11 and these did not correlate DNA methylation patterns with patient survival. In this pilot study, we evaluated the DNA methylomes of 15 osteosarcoma biopsy samples and correlated these methylation profiles with patient clinical data.…”
Section: Introductionmentioning
confidence: 98%